Analysis of The Influence of Work-Life Balance (WLB), Workload, and Social Support on Employee Performance at (PLTU) Asam Asam - Muhammad Yusuf Habibie; Sigit Hermawan; Wisnu Panggah Setiyono (Green Publisher Indonesia, 2025)
The performance of employees at PLTU Asam Asam, as a vital element in the company’s success in meeting national energy needs, is influenced by Work-Life Balance (WLB), Workload, and Social Support, which collectively play a crucial role in maintaining productivity, job satisfaction, and employee well-being amid high operational challenges. This study aims to analyze the influence of Work-Life Balance, Workload, and Social Support on employee performance at PLTU Asam Asam. Using a quantitative approach with a saturated sampling technique involving 183 employees, data were collected through a Likert scale and analyzed using SEM-PLS to examine the impact of factors such as working hours, knowledge management, and social support on employee job satisfaction. The findings reveal that Work-Life Balance (WLB), Workload, and Social Support significantly affect employee performance at PLTU Asam Asam. A good work-life balance enhances performance, while excessive workload can reduce it. Additionally, social support from the work environment plays a role in boosting motivation and productivity. These three factors explain 71.2% of the variation in employee performance, with the remaining portion influenced by other factors.